A Legal Perspective Toward Unlawful Acts in Tender Collusion in Indonesia - Puspaningrum, Galuh; Yasa, I Wayan; Putri, Linda Cristina (Media Iuris, 2025)
The research aims to compare and examine a case of tender conspiracy seeking similarities with or seen from the perspective of civil unlawful acts. Every business actor is prohibited from carrying out an activity that results in losses for other business actors and conducting fraudulent competition. The legal issues addressed in this research include reviewing one of the prohibited activities, namely the conspiracy of tenders stipulated in Article 22 of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition (Anti-Monopoly Law), from the elements of unlawful acts based on Article 1365 of the Civil Code (Civil Code). The legal issues in this study are, first, does the practice of bid rigging contain elements of unlawful acts, and what is the legal perspective on it, and second, what are the legal consequences for business actors proven to have engaged in bid rigging. This paper uses normative legal research, supported by primary and secondary legal materials and legal approaches are relevant to the legal issues under study, such as the approach to legislation, conceptual approach and comparative approach. The findings and discussion showed that bid rigging actions can be classified as unlawful acts, based on the following elements. First, the act of collusion with the intention to manipulate and ensure who will win the tender. Second, the act qualifies as unlawful, consisting of the elements of collusion, manipulation, and ensuring a specific business actor wins the tender, along with the element of unfair competition. Third, the element of fault is fulfilled on the part of the reported parties, in this case, the tender participants. Fourth, the practice negatively affects other business actors, both materially and immaterially, particularly in their opportunity to win the tender. Fifth, there is a proven causal relationship and impact of the bid rigging committed by the reported parties, resulting in harm to other business actors. In conclusion, bid rigging practices can be classified as unlawful acts as long as the elements of such acts are fulfilled.